Governança nas fundações de apoio às universidades federais brasileiras - Manso, Francisca Yanna Gonçalves de Carvalho (2015)
How Foundations Support occupy hum important space no current economic scenario, especially in the que regarding the support given to Federal Brazilian Universities. Although as Foundations Support not belong to the Public Administration, working with expressive public resources, so that in many situations, are required by legal force, to apply to the same standards as public sector entities and should be adequate, so as governance practices que contribute to the improvement of management. Based of this, this research is General Purpose analyze the level of adherence of Foundations of Federal Support to Brazilian Universities at Best Governance Practices For International Federation of Accountants (IFAC) and hair Brazilian Institute of Corporate Governance (IBGC). The search can be characterized as qualitative, descriptive, exploratory and bibliographic. Data collection was applied hum questionnaire structured, with 4 blocks, directed to managers of 60 foundations support. As for the results, there was a que 58% of foundations limit, through the statute of the Foundation, the acting executive; 80% of respondents stated that the board of trustees act monitoring, approving and discussing actions regarding to reach policies of organizational and governance practices fins. With the research, it was concluded que as foundations support are partially adherent at governance practices IFAC and make IBGC, so it is boded in at least 42% of the analyzed items related the board of trustees; 58% adherence to questions relation to the Performance of the Audit Committee; and 62% of Issues the Chief Executive.